The role of scout activities and learning environment at school toward students’ characters - Nelly Astuti; Fadhilah Khairani; Frida Destini; Sulistyawati Sulistyawati (Lighthouse Publishing, 2021)
This study aimed to determine the role of scout extracurricular activities toward student characters, between the learning environment at school and the student characters, and between scout extracurricular activities and the learning environment at school along with students’ characters. The research adopted an ex-post-facto correlation with a total population of 112 students and 54 of them were taken as samples. Observation and questionnaires were used for data collection. Product Moment Correlation and Multiple Correlation were undertaken to analyze the collected data. Based on the analysis, the results of the study indicated that there was a relationship between scout extracurricular activities and learning environment at school toward students’ characters.